Case Study of Unilever's Zero-Emission Target Realization - Buri, Zsolt; T. Kiss, Judit (International Journal of Engineering and Management Sciences, 2025)
This paper presents a detailed case study of Unilever’s strategy and progress toward achieving zero carbon emissions, focusing on Scope 1, 2, and 3 emissions. The study analyzes a 10-year time series of both financial and non-financial data to assess the relationship between sustainability indicators, such as greenhouse gas (GHG) emissions, total and renewable energy use, and the company’s operating profit. Forecasting techniques were applied to project future emission levels based on historical data, while correlation analysis was used to evaluate the relationships between key variables. The results show a strong positive correlation between total energy use and CO₂ emissions, highlighting the importance of energy efficiency in emission reduction efforts. However, no significant correlation was found between operating profit and CO₂ emissions or energy use, suggesting that sustainability initiatives have not yet had a measurable direct impact on profitability. Despite this, Unilever has demonstrated substantial progress toward its climate targets, including a 91% reduction in CO₂ emissions per ton of production (compared to a 2008 baseline) and the transition to 100% renewable electricity in many of its facilities. The study concludes that while sustainability measures may not immediately influence profit margins, they are essential for long-term competitiveness and corporate responsibility. This case provides valuable insights for firms aiming to integrate environmental performance into strategic decision-making.